Synthesis of novel and stable g-C3N4-Bi2WO6 hybrid nanocomposites and their enhanced photocatalytic activity under visible light irradiation. Issue 3 (28th March 2018) - Li, Haitao; Li, Na; Wang, Ming; Zhao, Beiping; Long, Fei
Abstract : Graphitic carbon nitride (g-C3 N4 ) nanosheets with a thickness of only a few nanometres were obtained by a facile deammoniation treatment of bulk g-C3 N4 and were further hybridized with Bi2 WO6 nanoparticles on the surface via a solvothermal method. The composite photocatalysts were characterized by powder X-ray diffraction, scanning electron microscopy, transmission electron microscopy, UV–vis diffuse reflection spectroscopy and X-ray photoelectron spectroscopy (XPS). The HR-TEM results show that the nano-sized Bi2 WO6 particles were finely distributed on g-C3 N4 sheet surface, which forms heterojunction structure. The UV–vis diffuse reflectance spectra (DRS) show that the absorption edge of composite photocatalysts shifts towards lower energy region in comparison with those of pure g-C3 N4 and Bi2 WO6 . The degradation of methyl orange (MO) tests reveals that the optimum activity of 8 : 2 g-C3 N4 -Bi2 WO6 photocatalyst is almost 2.7 and 8.5 times higher than those of individual g-C3 N4 and Bi2 WO6 . Moreover, the recycle experiments depict high stability of the composite photocatalysts. Through the study of the influencing factors, a possible photocatalytic mechanism is proposed. The enhancement in both photocatalytic performance and stability was caused by the synergistic effect, including the effective separation of the photogenerated electron-hole pairs at the interface of g-C3 N4 and Bi2 WO6, the smaller the particle size and the relatively larger specific surface area of the composite photocatalyst.